Estimation of pyrazinamidase activity using a cell-free In vitro synthesis of pnca and its association with pyrazinamide susceptibility in Mycobacterium tuberculosis - Daniel Rueda; Christine Bernard; Lucas Gandy; Estelle Capton; Rachid Boudjelloul; Florence Brossier; Nicolas Veziris; Mirko Zimic; Wladimir Sougakoff (International Journal of Mycobacteriology, 2018)
Background: The main mechanism of resistance to PZA in Mycobacterium tuberculosis relies on mutations on its pyrazinamidase/nicotinamidase. Recently, a rapid colorimetric test relying on the PCR-based in vitro-synthesized-PZase assay has been reported for PZase activity determination from clinical M. tuberculosis isolates but the assay has not been compared with other tests to evaluate PZA susceptibility in M. tuberculosis isolates. Methods: In this study, we have used the PCR-based in vitro-synthesized-PZase assay to analyze the specific pyrazinamidase (PZase) activity of PncA mutants and have correlated the results to the PZA susceptibility phenotype determined by culture in acidic agar medium at pH 6.0. A set of 23 clinical isolates displaying mutated pncA genes (11 PZA-resistant and 12 PZA-susceptible) and 55 PZA-susceptible clinical strains displaying a wild-type pncA gene were tested. Results: Among the 23 mutants tested, 4 corresponded to mutations not reported before (I5T, Y99S, T142R and P77L+V131G). Of the 11 PncA mutants expressed from PZA-resistant clinical isolates, 9 were expressed in vitro at yields > 50% relative to the wild type enzyme. Among them, 6 enzymes (T47P, H51P, H51R, H57D, L85R and T142R) showed no detectable activity, while the relative activities for the 3 others, V9A (27%), G97D (10%) and A146V (28%) were low compared to the wild-type PZase. The remaining two mutants, I5T and V9G, presented very low relative expression (5%) and relative activities values of 12 and 1%, respectively. Twelve mutants were expressed from PZA-susceptible isolates. Their expression was similar to the wild type enzyme and behaved as active pyrazinamidase with specific relative activities ranging from 34 to 314%. Finally, discrepant results were observed for two mutants, V7A and P62T. Conclusion: Thus, this study provides the proof of concept that the PCR-based in vitro-synthesized-PZase assay represents a promising rapid approach for the evaluation of PZA susceptibility based on the estimation of the relative PZase activity from clinical isolates.